The Hybrid Approach to Intervention of Chronic Total Occlusions - V. Rangan, Bavana; Kotsia, Anna; Christopoulos, George; Spratt, James; Rinfret, Stephane; Banerjee, Subhash; S. Brilakis, Emmanouil (Current Cardiology Reviews, 2015)
The “hybrid” approach to chronic total occlusion (CTO) percutaneous coronary intervention (PCI) was developed to provide guidance on optimal crossing strategy selection. Dual angiography remains the cornerstone of clinical decision making in CTO PCI. Four angiographic parameters are assessed: (a) morphology of the proximal cap (clear-cut or ambiguous); (b) occlusion length; (c) distal vessel size and presence of bifurcations beyond the distal cap; and (d) location and suitability of a retrograde conduit (collateral channels or bypass grafts) for retrograde access. Antegrade wire escalation is favored for short (<20 mm) occlusions, usually escalating rapidly from a soft tapered-tip polymer-jacketed guidewire to a stiff polymer-jacketed or tapered-tip guidewire. Antegrade dissection/re-entry is favored in long (≥20 mm long) occlusions, trying to minimize the dissection length by re-entering into the distal true lumen immediately after the occlusion. Primary retrograde approach is preferred for lesions with an ambiguous proximal cap, poor distal target, good interventional collaterals, and heavy calcification, as well as chronic kidney disease. The “hybrid” approach advocates early change between strategies to enable CTO crossing in the most efficacious, efficient, and safe way. Several early studies are demonstrating high success and low complication rates with use of the “hybrid” approach, supporting its expanding use in CTO PCI.
Keywords: Chronic total occlusion